2011
DOI: 10.1063/1.3592672
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain analysis and experimental examination of cumulative second-harmonic generation by primary Lamb wave propagation

Abstract: Within the second-order perturbation approximation, the physical process of cumulative second-harmonic generation by the primary Lamb wave propagation has been investigated in the time domain. Based on the preconditions that the transfer of energy from the primary Lamb wave to the double frequency Lamb wave is not zero and that the phase velocity matching condition is satisfied, we focus on analyzing the influence of mismatching of the group velocities on the generation of the second harmonic by propagation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 20 publications
2
39
0
3
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22][23][24][25][26] In the past years, some theoretical and experimental studies of nonlinear Lamb waves have been reported. [14][15][16][17][18][19][20][21][22][23][24][25][26] It is found that the generation of cumulative higher harmonics in Lamb waves is only possible under certain conditions due to their dispersive nature. [14][15][16]19,[21][22][23] Recently, some studies focus on using the effect of second-harmonic generation by the primary Lamb wave propagation to assess the early stage of damages in platelike structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23][24][25][26] In the past years, some theoretical and experimental studies of nonlinear Lamb waves have been reported. [14][15][16][17][18][19][20][21][22][23][24][25][26] It is found that the generation of cumulative higher harmonics in Lamb waves is only possible under certain conditions due to their dispersive nature. [14][15][16]19,[21][22][23] Recently, some studies focus on using the effect of second-harmonic generation by the primary Lamb wave propagation to assess the early stage of damages in platelike structures.…”
mentioning
confidence: 99%
“…[14][15][16]19,[21][22][23] Recently, some studies focus on using the effect of second-harmonic generation by the primary Lamb wave propagation to assess the early stage of damages in platelike structures. 17,18,20,[24][25][26] However, up to now, little work has been done on the relationship between the nonlinear Lamb waves and the microstructure evolutions in the damaged materials, such as dislocations, second phase precipitates, and micro-voids, even though it is of significance for a quantitative assessment of the damaged materials.…”
mentioning
confidence: 99%
“…Given a line source parallel to the ox axis, within second-order perturbation, the analytical solution of the cumulative secondharmonic of Lamb waves for Eq. (1) can be derived by the modal analysis method of waveguide excitation as 14,18,19 …”
Section: A Correlation Between Nonlinear Lamb Waves and Acoustic Nonmentioning
confidence: 99%
“…0021-8979/2014/115(4)/044914/11/$30.00 V C 2014 AIP Publishing LLC 115, 044914-1 potential advantage of using nonlinear Lamb waves to track creep damage is that they are capable of propagating long distances, thus making them an ideal candidate to interrogate large plate and shell structures for detecting and evaluating their early creep damages, including dislocation motions, precipitates variations, formation of micro-voids, multipoles, and micro-cracks. [14][15][16][17][18][19][20][21][22][23][24][25] In the past years, some theoretical and experimental studies of nonlinear Lamb waves have been reported. It is found that the generation of cumulative higher harmonics in Lamb waves is only possible under certain conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation